Reinforced concrete design - Mosley, W. H. (William Henry) (Macmillan, 1999)
A straightforward introduction to the principles and methods of design for concrete structures. This edition has been updated to incorporate changes introduced in the 1997 version of BS8110 and to include new material such as pile cap design and a new chapter on composite construction.